/

Which of the following statements demonstrates a negative correlation between two variables?

A. People who play baseball more tend to have more hits

B. Shorter people tend to weigh less than taller people

C. Tennis balls that are older tend to have less bounce

D. Cars that are older tend to have higher mileage

Answer Explanation:

A negative correlation means as one variable increases, the other variable decreases or as one variable decreases, the other variable increases. Based on this definition, we analyze the given statement as follows:

People who play baseball more tend to have more hits is POSITIVE CORRELATION

Shorter people tend to weigh less than taller people is a POSITIVE CORRELATION

Tennis balls that are older tend to have less bounce is a NEGATIVE CORRELATION

Cars that are older tend to have higher mileage is a POSITIVE CORRELATION

Therefore, the Correct Answer is C.

More Questions on TEAS 7 Math

  • Q #1: Which of the following expressions represents the sum of three times a number and eight times a different number?

    A. 3x+8y

    B. 8x+3x

    C. 3x-8y

    D. 8x-3y

    Answer Explanation

    Let two numbers be x and y. Then

    Three time a number=3x

    Eight times a different number = 8y

    Sum of the two is 3x+8y

  • Q #2: Which of the following is the area of the largest circles that can fit entirely inside a rectangle that measures 8 centimeters by 10 centimeters?

    A. 18π cm2

    B. 10 π cm2

    C. 16 π cm2

    D. 8 π cm2

    Answer Explanation

    To find the area of the largest circle that fits in the rectangle, we need to determine the area of a circle with a diameter of 8 cm or less to fit on the rectangle with the given measurements as illustrated below.

    Area of circle=  πr2 

    Radius of circle, r=8cm/2=4cm

    Then, area of the largest circle is:

    Area of circle=  π*4 cm *4 cm =16π cm2

  • Q #3: (x/y)-z=rw Solve for x in the equation above.

    A. X=y(z+rw)

    B. X=rw(y-z)

    C. X=rwy+z

    D. X=rwy-z

    Answer Explanation

    Given the equation (x/y)-z=rw, we make x the subject of the formula as follows:

    (x/y)-z=rw

    Add z to both sides of the equation

    (x/y)-z+z=rw+z

    (x/y)=rw+z

    Multiply both sides by y

    (x/y)*y=y(rw+z)

    X=y(rw+z)

    Rearranging the equation results in:

    X = y(z+rw)